TELEMEDICINE — PROSPECTS AND DIFFICULTIES BEFORE A NEW DEVELOPMENT STAGE - A. A. Baranov; E. A. Vishneva; L. S. Namazova-Baranova (Педиатрическая фармакология)
The article is devoted to telemedicine — an applied sphere of medical science linked with development and practical application of rendering distant medical care and specialized information, sharing methods on the basis of modern information and telecommunication technologies. This landmark sphere of medical care organization and rendering has already become an inalienable part of modern public health. The aim of telemedicine is to provide quality medical care to anyone regardless of their location and social status. Telemonitoring as a future technology is already finding wide use in spheres where constant domiciliary medical care is required. It is used in neonatology to observe infants with low and extremely low body weight during the antenatal period, in cardiology — to control the condition of a patient with an implantable device (pacemaker or cardioverter defibrillator); this method is also widely used in other spheres ofmedicine. It is possible to organize advisory assistance to medical care rendering through employing highly qualified specialists of largescalemedical centers in case of emergency. Extra possibilities of applying new medical approaches, which considerably expand the range of patients under outpatient observation and reduce the number of patients’ visits to clinics, appeared owing to the application of information technologies in public health. The article gives a detailed account of various aspects of telemedicine.